Adaptation to the international business environment: a resource advantage perspective - Ferreira, Manuel Portugal (2021)
This paper discusses the importance of the adaptation of the firm to the International Business Environment. Using concepts from the literature on resource advantage, we posit that the firms' adaptation capability to different International Business Environments is a valuable, difficult to imitate, non-tradeable, rare but not scarce and path dependent resource. We further suggest that adaptation to International Business Environment is a non-substitutable core source of competitive advantage for the multinational enterprises, developed over time through the firms experiences and built into their routines. In line with this argument, some propositions are formulated. We conclude with a broad discussion and suggesting some avenues for future research\.